Anthropomorphism in hospitality and tourism: A systematic review and agenda for future research. (September 2022) - Ding, Anni; Lee, Rachel Hyunkyung; Legendre, Tiffany S.; Madera, Juan
Abstract: Anthropomorphism has been identified as an effective marketing and communication tool in the hospitality and tourism industry. However, the application of anthropomorphism is fraught with a variety of definitions, contradictory findings, and different contexts, resulting in a lack of synthesized understanding of anthropomorphism. This study presents a systematic review of the anthropomorphism research in the hospitality and tourism literature from the past two decades to identify trends in the literature and to propose directions for future research on anthropomorphism. Three streams emerged from the literature: (1) Technology anthropomorphism; (2) Brand anthropomorphism; and (3) Product anthropomorphism. The results indicate that brand anthropomorphism and product anthropomorphism are understudied in the hospitality and tourism literature despite their theoretical applicability and potential. By identifying limitations in current literature and comparing it with anthropomorphism studies in other fields, this study further draws meaningful directions for future research.